Intravital Multiphoton Microscopy of the Ocular Surface: Alterations in Conventional Dendritic Cell Morphology and Kinetics in Dry Eye Disease - Jamali, Arsia; Seyed-Razavi, Yashar; Chao, Cecilia; Ortiz, Gustavo; Kenyon, Brendan; Blanco, Tomas; Harris, Deshea L.; Hamrah, Pedram (Frontiers in Immunology, 2020)
Dry eye disease (DED) is a multifactorial disease of the ocular surface, characterized by loss of tear film homeostasis and ocular symptoms, in which neurosensory abnormalities have recently been shown to play an etiological role. Although the role of inflammation has been widely studied in DED, the kinetics of immune cells of the ocular surface in this complex disease are hereto unclear. Herein, we utilized intravital multi-photon imaging transgenic mice to investigate the 3D morphology and kinetics of conventional dendritic cells (cDCs), and the role of ocular surface sensory nerves in regulating them in both the naïve state and experimental DED. DED mice had significantly lower tear secretion (p<0.01), greater corneal fluorescein staining (p<0.001), and higher cDC density in the ocular surface (p<0.05), compared to naïve mice. DED mice showed morphological alterations of cDCs in the limbus, exhibiting smaller surface area (p<0.001) and volume (p<0.001) compared to naïve mice. Further, corneal cDCs showed greater sphericity in DED mice compared to naïve mice (p<0.01). In addition, limbal cDCs displayed significantly increased migratory kinetics in DED, including mean track speed, 3D instantaneous velocity, track length, and displacement, compared to naïve mice (all p<0.05). In mice with DED, cDCs showed a higher meandering index in the limbus compared to central cornea (p<0.05). While cDCs in contact with nerves demonstrated a larger surface area (p<0.001), volume (p<0.001), and greater sphericity (p<0.05) as compared to cDCs not in contact with nerves in naïve mice, these differences were not seen during DED. Importantly, cDCs in contact with nerves during DED had a decreased track length, displacement, mean track speed, and 3D instantaneous velocity compared to those not in contact with nerves (all p<0.05). Taken together, we present in vivo evidence of altered cDC kinetics and 3D morphology in DED. Further, apparent neuronal contact significantly alters cDC kinetics and morphological characteristics, indicating they may play a direct role in mediating immune response in DED.